Diaqua(1,4,8,11-tetraazacyclotetradecane-kappa 4 N 1,N 4,N 8,N 11)copper(II) bis(4-methylbenzoate) monohydrate - Tajidi, N.S.A.; Abdullah, N.; Arifin, Z.; Tan, K.W.; Ng, S.W. (International Union of Crystallography, 2010)
The CuII atom in the title salt, [Cu(C(10)H(24)N(4))(H(2)O)(2)](C(8)H(7)O(2))(2)center dot H(2)O, is chelated by the four N atoms of the 1,4,8,11-tetraazacyclotetradecane (cyclam) ligand and is coordinated by two water molecules in a Jahn-Teller-type of tetragonally distorted octahedral geometry. The cations, anions and lattice water molecules are linked by N-H...O and O-H...O hydrogen bonds to form a layer structure parallel to (001).